Effect of colored lenses on muscular performance - Fisher, J.; D`amario, D.; Small, C.; Stopforth, M. (The Journal of Sports Medicine and Physical Fitness, 2015)
AIM: The effect of color on physiological parameters appears well documented. However, methodological weaknesses and limitations to practical application suggest it to be substantially under researched with regard to physical performance. The aim of this study was to consider the effects of red, blue and clear (control) colored lens glasses on a muscular endurance task.